2014
DOI: 10.1364/ol.39.006755
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-optic magnetometry with randomly oriented spins

Abstract: We demonstrate fiber-optic magnetometry using a random ensemble of nitrogen-vacancy (NV) centers in nanodiamond coupled to a tapered optical fiber, which provides a waveguide delivery of optical fields for the initialization, polarization, and readout of the electron spin in NV centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 20 publications
6
21
0
Order By: Relevance
“…The effect of a non-aligned magnetic field is to induce spin flips in the NV centers, thereby reducing fluorescence with increasing magnetic field strength, which is in agreement with previous observation 30 . This effect offers all-optical detection of external magnetic fields in the absence of RF fields with our ND-doped fiber approach.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effect of a non-aligned magnetic field is to induce spin flips in the NV centers, thereby reducing fluorescence with increasing magnetic field strength, which is in agreement with previous observation 30 . This effect offers all-optical detection of external magnetic fields in the absence of RF fields with our ND-doped fiber approach.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, our ND/tellurite glass has been used to realize an inherently magnetic field sensitive optical fiber with sensitivity of order . Such sensitivity is comparable to that achieved in fiber taper platforms with NDs coated on the taper surface 29 , 30 . Using a theoretical model that qualitatively reproduces the experimental ODMR results, we have shown that the fiber background fluorescence has a significant impact on intensity and contrast of the ODMR peaks and hence on magnetic sensitivity.…”
Section: Discussionsupporting
confidence: 68%
“…We have developed an efficient single photon source with a coupling efficiency of more than 7% by locating CdSe/ZnS quantum dots on the nanofiber [13]. In addition to this demonstration, there have been many coupling experiments between nanofibers and single light emitters such as quantum dots [14,15], molecules [16], nitrogen vacancy centers in diamond [17][18][19][20], and hexagonal boron nitride [21].…”
Section: Introductionmentioning
confidence: 99%
“…The trade-off between the spatial resolution and sensitivity is crucial for the performance of fiber-optic NV-diamond magnetometers. While a submicron resolution can be achieved with NV-diamond nanoparticles coupled to the tip of a tapered fiber [14,15], real-life applications, including optical magnetometry and thermometry of biological cells, often dictate a more durable design of a fiber-NV-diamond interface. As shown in the earlier work [11], a fiber-optic probe integrating an NVdiamond microcrystal and a standard multimode optical fiber can enable magnetic field imaging with a ∼150 μm spatial resolution and sensitivity of the order of 10 pT • Hz −1∕2 .…”
mentioning
confidence: 99%